Analisis Peranan Etika Dalam Penerapan Akuntabilitas Dan Transparansi Pelayanan Publik - Serli Marshanda; Sayidah Nurul Zikri; Cattleya Selma Concetta Pardede; Delvian Narendra; Yulia Hanoselina; Rahmadhona Fitri Helmi (CV. ITTC INDONESIA, 2024)
Public administration ethics has a very important role in creating accountability and transparency by public officials. This study aims to analyze the influence of public administration ethics in improving the quality of public services. The research method used is a qualitative method through a literature analysis approach to journals, articles, books and related regulations. The results of the study show that the implementation of public administration ethics can increase accountability and transparency, thereby encouraging the creation of good governance. This study recommends an evaluation of ethical principles in public service and improving a culture of integrity in leadership and optimizing information disclosure to the public through technology.